The experiences of gender diverse and trans children and youth considering and initiating medical interventions in Canadian gender-affirming speciality clinics. Issue 4 (2nd October 2019) - Pullen Sansfaçon, Annie; Temple-Newhook, Julia; Suerich-Gulick, Frank; Feder, Stephen; Lawson, Margaret L.; Ducharme, Jennifer; Ghosh, Shuvo; Holmes, Cindy; ,
Abstract: Background : Canadian specialty clinics offering gender-affirming care to trans and gender diverse children and youth have observed a significant increase in referrals in recent years, but there is a lack of information about the experiences of young people receiving care. Furthermore, treatment protocols governing access to gender-affirming medical interventions remain a topic of debate. Aims: This qualitative research aims to develop a deeper understanding of experiences of trans youth seeking and receiving gender-affirming care at Canadian specialty clinics, including their goals in accessing care, feelings about care and medical interventions they have undergone, and whether they have any regrets about these interventions. Methods : The study uses an adapted Grounded Theory methodology from social determinants of health perspective. Thirty-five trans and gender diverse young people aged 9 to 17 years were recruited to participate in semi-structured interviews through the specialty clinics where they had received or were waiting for gender-affirming medical interventions such as puberty blockers, hormone therapy, and surgery. Results: Young people felt positively overall about the care they had received and the medical interventions they had undergone, with many recounting an improvement in their well-being since starting care. Most commonly shared frustrations concerned delays in accessing interventions due to clinic waiting lists or treatment protocols. Some youth described unwanted medication side-effects and others said they had questioned their transition trajectory at certain moments in the past, but none regretted their choice to undergo the interventions. Discussion : The results suggest that trans youth and gender diverse children are benefiting from medical gender-affirming care they receive at specialty clinics, providing valuable insight into their decision-making processes in seeking care and specific interventions. Providers might consider adjusting aspects of treatment protocols (such as age restrictions, puberty stage, or mental health assessments) or applying them on a more flexible, case-by-case basis to reduce barriers to access.